PENGARUH MOTIVASI WISATAWAN KOTA LAMA SEMARANG PADA PERILAKU MEMBACA INFORMASI WISATA SEJARAH - Surya Prabhaswara, Fauzan; Surayya Ulfa, Nurist; Naryoso, agus (Interaksi Online, 2024)
Historical tourism, especially in Semarang Old Town, is increasingly popular. However, despite various efforts to provide historical information through various media, tourists' interest in reading this information still needs to be improved. This study aims to reveal the influence of tourist motivation on the behavior of reading historical information in Semarang Old Town. By understanding the factors that influence tourist motivation, it is hoped that effective strategies can be found to increase tourist interest in delving deeper into the history and culture of Semarang Old Town. This study used a quantitative explanatory method with a purposive sampling technique involving 200 respondents. The results of the study showed that social motivation and cultural motivation had no effect on the behavior of reading historical information. Meanwhile, prestige motivation had a fairly strong positive effect on the behavior of reading historical information.